Diversity and Uniqueness of Sovereign Sukuk Issuance: Indonesian Experience - Supyadillah, Asep; ., Hidayatulloh; Arif, Zainal (Journal of Ecohumanism, 2025)
The main objectives of this paper are (1) to provide an overview of the diversity of retail-type sovereign sukuk, and (2) to explore the uniqueness of characteristics of each retail type of sovereign sukuk issuance. The research method uses qualitative research - descriptive with a socio-juridical and inductive approach. All sources of data were obtained from the literature in the form of documents and laws and regulations as well as explanations from Ministry of Finance, Republic of Indonesia as the party authorized for the issuance of the retail type of sovereign sukuk. Data analysis was carried out using a content analysis model of the process and realization of Retail Sukuk issuance. Finally, the findings of this study indicate that the issuance of retail-type state sukuk in Indonesia is based on the state's need to fulfill deficiencies in the State Revenue and Expenditure Budget, as well as the public's need for alternative investments and efforts to optimize the potential of Islamic social funds. The existence of Cash Waqf Linked Sukuk (CWLS) in addition to Savings Sukuk and Retail State Sukuk, it indicates the adoption of the need for sukuk from philanthropic funds which are uniquely Indonesian.